Як можливі “дві” філософії права? - Ониськів, М.М.; Рижко, В.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2003)
Современная философия права считается структурной частью как философии, так и юриспруденции. Это порождает не до конца разрешенный вопрос о статусе философии права как научной дисциплины. В статье анализируется проблема взаимоотношения философского и юридического аспектов философии права, исходя из двух ключевых функций философии: методологической и юридической. Contemporary philosophy of law is considered to be a structural part of both, philosophy and jurisprudence.
This originates a yet unsolved issue of the status of philosophy of law as a field of academic study. The article presents an analysis of the issue of the interrelation between philosophical and juridical aspects of
philosophy of law, proceeding from two key functions of philosophy, namely, methodological and juridical.